Singlet-excited dioxygen O2(a1Δg) and organic pollutants in marine waters beneath the Sun - BF Minaev (Annals of Marine Science - Peertechz Publications, 2023)
The ground state dioxygen has a triplet spin state O2(X3Σg). The singlet excited O2(a1Δg) dioxygen possesses an excess energy of 22 kcal/mole and is highly reactive with respect to organic matter since all organic molecules have also singlet ground states with all spins paired; their reactions with O2(a1Δg) are not forbidden by spin selection. The chromophoric pollutants in sea waters under sun irradiation can generate O2(a1Δg) and other reactive oxygen species which could oxidase many wastes. This review describes mechanisms of O2(a1Δg) interaction with organic pollutants in seawater with black carbon dispersion and with corals.